2016
DOI: 10.3390/ijms17101625
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity and Cytokine Imbalance in Inherited Epidermolysis Bullosa

Abstract: In order to evaluate the serum anti-skin autoantibodies and cytokine concentrations in patients with different epidermolysis bullosa (EB) types and severity, 42 EB patients and 38 controls were enrolled. Serum anti-skin antibodies were significantly higher in the patients than in the controls (p = 0.008, p < 0.001, p < 0.001, p < 0.001 and p < 0.001 for desmoglein 1 (DSG1) desmoglein 3 (DSG3), bullous pemphigoid 180 (BP180), BP230 and type VII collagen (COL7), respectively). The same trend was observed for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
1
38
1
1
Order By: Relevance
“…Interestingly, depletion of collagen-VII from immunodeficient mice (NSG mice) results in a less severe disease phenotype. Taken together, these studies emphasize the critical role played by the immune cells in exacerbating the disease condition (Esposito et al, 2016).…”
Section: Skin Diseasesmentioning
confidence: 79%
“…Interestingly, depletion of collagen-VII from immunodeficient mice (NSG mice) results in a less severe disease phenotype. Taken together, these studies emphasize the critical role played by the immune cells in exacerbating the disease condition (Esposito et al, 2016).…”
Section: Skin Diseasesmentioning
confidence: 79%
“…Moving towards RDEB patients, a study of Esposito and coll. demonstrated that circulating levels of antibodies against skin proteins and pro-inflammatory cytokines, in particular, IL-6, are significantly higher with respect to healthy controls, and correlate with disease severity [71]. Of note, IL-6 levels were significantly associated with EB extension (localized or generalized disease), disease severity and anti-skin antibodies levels [71].…”
Section: Dystrophic Ebmentioning
confidence: 99%
“…IL‐31 is a known pruritogen; however, no correlation was observed between the IL‐31 haplotype and EBP . Patients with EB display increased IL‐1β, IL‐2, IL‐6, IL‐10, tumour necrosis factor‐β and interferon‐γ levels, which seem to be higher in recessive DEB and generalized forms than in dominant and localized subtypes . IL‐6 and IL‐12 levels were found to correlate with disease severity .…”
mentioning
confidence: 93%